PENGARUH KOMPOS DAN BERBAGAI PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TEMULAWAK (CURCUMA XANTHORRHIZA) - Sugiharto, A.; Widawati, Sri (JURNAL BIOLOGI INDONESIA, 2005)
ABSTRACTThe Influence of Compos and Several Biofertilizers on the Growth and the Harvesting ofTemulawak (Curcuma xanthorrhiza). Curcuma xanthorriza is one of the potentialmedicinal plants. Usually this plant is planted only as additional plant among the mainhorticultural plants. This plant is used as medicine plant, and usually grown not in fertile soils.So, this research tried to use the additional fertilizer such as compost and the potentialmicrobes. The aim of the research was to know the influence of the compost and the potentialisolates on the growth of the Curcuma xanthorrhiza. The research had been done at the greenhouse with Randomized Completely Design, by using polybag with 20 cm diameter. Therewas three replications. The results analyzed with ANOVA method, and Duncan Test at 0,05.The used soil was podsolik yellowish red that collected from Darmaga, Bogor. The resultshowed that the use of compost and biofertilizer increased the harvesting of the tubers from15,76% to 52,79%. The using of either BPP isolates or the mycorrhyza, increased the driedweigh of tubers of Curcuma xanthorrhiza.Keywords : Compost, potential microbes, Curcunla xanthorrhiza